2001
DOI: 10.1159/000046268
|View full text |Cite
|
Sign up to set email alerts
|

IgA Nephropathy and Pulmonary Hemorrhage in an Adult

Abstract: IgA nephropathy is the most common glomerular disease worldwide, but is generally renal limited or associated with a rash. Pulmonary hemorrhage has been very uncommonly associated with IgA nephropathy, although it is frequently seen in other glomerulonephritides. We describe a well-proven case of IgA nephropathy associated with pulmonary hemorrhage, in which immunosuppressive medication was administered. We also review the literature to make a case for immunosuppression in these rare patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 10 publications
0
18
1
Order By: Relevance
“…[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] We excluded one report as no renal biopsy was done to establish the diagnosis of IgAN. 37 Our final review had 23 patients in 19 case reports; this included 19 reports of DAH, 28,29,[33][34][35][38][39][40][41][42][43][44][45][46][47] two reports of interstitial lung disease 31,32 and organizing pneumonia 30,36 each (Table S1). Two patients had findings consistent with organizing pneumonia on SLBx, although this was reported as bronchiolitis obliterans or immune complex pneumonitis; 30,36 both these patients had demonstrable IgA on surgical lung biopsy, indicating causality of this association.…”
Section: Our Data and Results Of Systematic Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] We excluded one report as no renal biopsy was done to establish the diagnosis of IgAN. 37 Our final review had 23 patients in 19 case reports; this included 19 reports of DAH, 28,29,[33][34][35][38][39][40][41][42][43][44][45][46][47] two reports of interstitial lung disease 31,32 and organizing pneumonia 30,36 each (Table S1). Two patients had findings consistent with organizing pneumonia on SLBx, although this was reported as bronchiolitis obliterans or immune complex pneumonitis; 30,36 both these patients had demonstrable IgA on surgical lung biopsy, indicating causality of this association.…”
Section: Our Data and Results Of Systematic Searchmentioning
confidence: 99%
“…Dyspnea (84%), hemoptysis (74%), cough (53%) and fever (47%) were the most common presenting complaints; 26.3% (5/19) had prominent symptoms suggestive of a connective tissue disease that was excluded on subsequent evaluation 33,34 or had an inactive connective tissue disease. 38,44 Simultaneous involvement of both kidneys and lungs was the most common presenting manifestation (42%); 29,34,35,38,40,41,45 one-third (37%) had prior diagnosed kidney disease 39,42,46,47 or undiagnosed IgAN 33 before presenting with PRS. In 21%, presentation was with alveolar hemorrhage.…”
Section: Our Data and Results Of Systematic Searchmentioning
confidence: 99%
“…Lung biopsy immunofluorescence staining was negative for our patient, but findings suggestive of pulmonary capillaritis on an open lung biopsy, together with IgA nephropathy clearly demonstrated on kidney biopsy, make this association highly likely in our patient. In previously published case reports of IgA nephropathy and pulmonary capillaritis, only one case reported IgA deposits of glomerular basement membrane, mimicking Goodpasture's disease [4] and exhibiting a similar pathology in the lung. The remainder of the cases did not have IgA deposits demonstrated in the lung.…”
Section: Discussionmentioning
confidence: 97%
“…There have been 11 cases in seven case reports that describe pulmonary hemorrhage in IgA nephropathy [2][3][4][5][6][7][8]; however, there has been only one pediatric case described previously. Yum et al [8] reported a 17-year-old boy who had recurrent respiratory illness, hemosiderin-laden macrophages on lung biopsy, and renal failure due to IgA nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation